The Existence of Natural Lexicons in ‘Awig-Awig’ Tenganan Pegringsingan Bali: An Ecolinguistic Approach - Mirsa Umiyati (Universitas Udayana, 2020)
Tenganan Pegringsingan Village, as one of the original villages in Bali, has a local wisdom characteristic that is agreed upon by its citizens. Local wisdom is included in the 'awig-awig' (local regulation) village in the form of verbal texts that aim to preserve the flora and fauna of extinction. This study aims to determine the type of flora-fauna lexicon found in 'awig-awig' of the village, and to know the customary restrictions and fines that are set for residents who break them. This research is a qualitative descriptive method using 'awig-awig' as research data and analyzing data through literature review. The results of the analysis found 39 lexicons of flora and fauna that are prohibited from being cut down/killed. The entire lexicon is divided into 9 categories, namely fruit, trees, leaves, tubers, rhizomes, seeds, roots, animals and flowers. Each amounted to 7 pieces, 11 trees, 2 leaves, 5 tubers, 1 rhizome, 1 seed, 1 root, 9 animals and 2 flowers. This study recommends collaboration with various parties to preserve the ecotex contained in the 'awig-awig' village of Tenganan Bali.